The Effect of a Combination Progressive Muscle Relaxation and Foot Massage on Improving Sleep Quality in the Elderly - Nabila Putri Wahyuni; Joko Wiyono; Dyah Widodo (PROFESSIONAL HEALTH JOURNAL, 2026)
A periodic and continuous lack of sleep can have a direct impact on the health of the elderly. Both pharmacological and non-pharmacological therapies can be utilized to treat poor sleep quality in this population. Progressive Muscle Relaxation and Foot Massage are relaxation therapies that are often utilized to address poor sleep quality among the elderly. The purpose of this study was to determine the effect of a combination of progressive muscle relaxation and foot massage on improving sleep quality in the elderly. The research design used was pre-experimental, with a sampling method used purposive sampling and 20 respondents. The instrument used was the Pittsburgh Sleep Quality Index (PSQI). The results showed that before the combined therapy was administered, all respondents experienced poor sleep quality. After the combined therapy was given to the respondents seven times over one week, all respondents experienced good sleep quality. Wilcoxon pre-test and post-test showed a Sig. (2-tailed) value of 0.000 < 0.05, indicating that the research hypothesis was acknowledged. Therefore, the combination of progressive muscle relaxation and foot massage had a significant effect on improving sleep quality in the elderly. This therapy is recommended to be carried out routinely and further studied to explore other variables and factors that affect sleep quality in the elderly.